2006
DOI: 10.1111/j.1462-5822.2005.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Fimbria-dependent activation of pro-inflammatory molecules in Porphyromonas gingivalis infected human aortic endothelial cells

Abstract: SummaryEpidemiological studies support that chronic periodontal infections are associated with an increased risk of cardiovascular disease. Previously, we reported that the periodontal pathogen Porphyromonas gingivalis accelerated atherosclerotic plaque formation in hyperlipidemic apoE -/-mice, while an isogenic fimbria-deficient (FimA-) mutant did not. In this study, we utilized 41 kDa (major) and 67 kDa (minor) fimbria mutants to demonstrate that major fimbria are required for efficient P. gingivalis invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 104 publications
(129 reference statements)
5
110
0
Order By: Relevance
“…Oral bacteria can enter the circulation and cause bacteraemia by actively crossing the periodontal epithelium [1820], or by being inoculated through mechanical procedures, including periodontal debridement, flossing and brushing [21,22]. Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833]. Studies in a variety of animal models have demonstrated that recurrent bacteraemia or oral administration with P. gingivalis can enhance atherogenesis [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Oral bacteria can enter the circulation and cause bacteraemia by actively crossing the periodontal epithelium [1820], or by being inoculated through mechanical procedures, including periodontal debridement, flossing and brushing [21,22]. Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833]. Studies in a variety of animal models have demonstrated that recurrent bacteraemia or oral administration with P. gingivalis can enhance atherogenesis [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Erythromycin (1.0 g/ml) and tetracycline (2.0 g/ml) were added according to the selection requirements of the strains (30). Fimbriae were prepared according to a modification of the method described by Arai et al (31).…”
Section: Purification Of the Major And Minor Fimbriae Of P Gingivalismentioning
confidence: 99%
“…Using major and minor fimbriae mutants we demonstrated that major fimbriae are required for P. gingivalis invasion of HAEC and that only invasive P. gingivalis strains induced the production of proinflammatory molecules IL-1␤, IL-8, MCP-1, ICAM-1, VCAM-1, and E-selectin (30). Our work demonstrated that following major fimbriae-mediated initial attachment, the minor fimbriae play an important role in more intimate attachment facilitating endocytosis of the bacteria (30). The purified native forms of the major and minor fimbriae induced chemokine and adhesion molecule expression similar to invasive P. gingivalis, but failed to elicit IL-1␤ production.…”
mentioning
confidence: 99%
“…Increased levels of IL-6 and IL-8 correlate with prognosis in patients with the risk of coronary heart disease (Hartford et al, 2006). Furthermore, several in vitro experiments have shown that bacterial products of P. gingivalis, such as fimbriae, LPS and gingipains, promote IL-6 and IL-8 production in gingival fibroblasts and epithelial cells (Matsushita et al, 2006;Takahashi et al, 2006;Roth et al, 2007).…”
Section: Hgp44 From P Gingivalis Inducing Huvecsmentioning
confidence: 99%